La sustancia y el contexto de las ofrendas rituales de la cerámica paracas - DeLeonardis, Lisa (2013)
The Paracas (900 BC-AD 1) of south coastal Peru are widely recognized for ceramics bearing patterned designs created fromincised clay that was often post-fire painted. Analyses of containers, effigies, figurines and musical instruments recovered intactin tombs, have centered largely on temporal and iconographic concerns, and in evaluating prestige. A number of archaeologicalcontexts offer an alternative view of ceramics and their role in public and domestic spheres. In this paper, the role of ceramics inritual offerings is discussed and analyzed in tandem with the other forms and mediums they accompany. The contexts for theseofferings differ from those of funerary ritual in which whole vessels are placed with the dead. These analyses indicate that the endcycle of ceramics is diverse, that their substance is valued in whole and fragmentary form, and that their spatial orientation issignificant. Insights are offered into how ceramics as substances interact and complement other materials in offerings and howthis bears upon our interpretation of specific iconographies and design symbols and their respective meanings.